An Overview of Causes and Control Measures of Obesity in Small Animals - Tawfeeq, Mohammad Monir (Journal of Natural Sciences – Kabul University, 2022)
Obesity is characterized by abnormal or excessive fat accumulation in the body, leading to significant health issues in humans and animals. In animal medicine, obesity is particularly relevant for small animals and horses, which are more prone to this condition. Several factors contribute to obesity, including imbalances in food intake that disrupt energy balance, polyphagia, and inactivity. Various methods are available for diagnosing or measuring body conditions in small animals. Additionally, multiple approaches are employed to treat and control obesity. This article discusses the causes, diagnostic measures, and control methods for obesity in small animals.